2013
DOI: 10.1111/jpn.12057
|View full text |Cite
|
Sign up to set email alerts
|

Post‐natal changes inMCT1 expression in the forestomach of calves

Abstract: The monocarboxylate transporter 1 (MCT1) has been demonstrated to be involved in the transfer of short-chain fatty acids (SCFA) and/or their intraepithelial metabolites from the rumen to the blood. As MCT1 plays a role in SCFA transfer, it is assumed that SCFA are the main substrates influencing its expression. However, there are hints that MCT1 may also be expressed during the early life of the animal when SCFA are not released in the forestomach. To figure out whether MCT1 expression in the forestomach is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
4
9
1
Order By: Relevance
“…Similar to our findings, Pfannkuche et al. () did not find the differences in MCT1 protein expression between dorsal and ventral sac of rumen. Furthermore, those authors found substantial basal MCT1 protein expression in first day of calves' life, which increased during next 4 days although calves had no access to solid feed.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Similar to our findings, Pfannkuche et al. () did not find the differences in MCT1 protein expression between dorsal and ventral sac of rumen. Furthermore, those authors found substantial basal MCT1 protein expression in first day of calves' life, which increased during next 4 days although calves had no access to solid feed.…”
Section: Discussionsupporting
confidence: 93%
“…As forestomachs are not developed in newborn ruminants, the increase in MCT1 expression in the rumen epithelial cells within first weeks of calves' life is not surprising and supports the results of other studies (Kirat et al., ; Koho et al., ; Oba et al., ; Pfannkuche et al., ). For example, Oba et al.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations